Accuracy of diagnoses of HIV-related oral lesions by medical clinicians. Findings from the Women’s Interagency HIV Study - Hilton JF, Alves M, Anastos K, Canchola AJ, Cohen M, Delapenha R, Greenspan (Blackwell Synergy, 2001)
To determine if medical clinicians are as accurate as dental clinicians in recognizing diagnostic characteristics of HIV-related oral lesions.